Support System In Determining Final Evaluation Supervisor And Examiner With Best Worst Method - Rudy Tandra; Heriyanto; Muhammad Diponegoro (Jurnal Mantik, 2022)
Final evaluation is a scientific work that is a requirement for students of the Politeknik Negeri Pontianak (Polnep) Business Administration Major to obtain an academic degree. As the person in charge of a final evaluation, supervisors and examiners have an important role in ensuring students are able to create a qualified final evaluation. Therefore, the diversity of titles and fields of final evaluation proposed by students needs to be combined with lecturers who have synchronized scientific disciplines and experiences. The manual determination of supervisors and examiners has the opportunity to be affiliated with subjective factors. The support system, which can essentially be used as a guide, explanation and reinforcement of a decision, has the opportunity to eliminate subjective factors that arise during decision making. The design of the support system was carried out based on five criteria that were calculated with a multi-criteria decision-making method, namely the Best Worst Method (BWM). Based on the results of system testing with 40 lecturer data and 231 student final evaluation proposal data, the support system could recommend supervisors and examiners that were in accordance with the student’s proposed final evaluation field.